Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1038/ki.2009.399
|View full text |Cite
|
Sign up to set email alerts
|

In patients with type 1 diabetes and new-onset microalbuminuria the development of advanced chronic kidney disease may not require progression to proteinuria

Abstract: Systematic study of the course of renal function decline and progression to proteinuria in patients with type 1 diabetes and new onset microalbuminuria has not been reported. From the 1080 participants with normoalbuminuria enrolled in the 1st Joslin Kidney Study, we identified 109 who developed new onset microalbuminuria in the first four years of observation and followed 79 for a subsequent 12.4±1.4 years to estimate glomerular filtration rate by the four-variable MDRD formula (GFRMDRD) and the course of mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
176
1
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 251 publications
(197 citation statements)
references
References 41 publications
(46 reference statements)
9
176
1
8
Order By: Relevance
“…In Pima Indians with type 2 diabetes, RFD occurs frequently before the onset of macroalbuminuria, as it does in type 1 diabetes (3)(4)(5). Progression to ESRD, however, is strongly dependent on progression to macroalbuminuria.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In Pima Indians with type 2 diabetes, RFD occurs frequently before the onset of macroalbuminuria, as it does in type 1 diabetes (3)(4)(5). Progression to ESRD, however, is strongly dependent on progression to macroalbuminuria.…”
Section: Discussionmentioning
confidence: 98%
“…The risk of progressing to ESRD is greatest in patients with macroalbuminuria and intermediate in those with microalbuminuria relative to normal ACR (1). Identifying which patients with microalbuminuria are most likely to develop more advanced kidney disease is difficult, because many patients with microalbuminuria regress to normal urinary albumin excretion during follow-up (1,2), and progression of kidney disease may not depend on progression to macroalbuminuria (3).…”
Section: Introductionmentioning
confidence: 99%
“…Assessments of cardiac autonomic nerve function were performed for a subset of 370 (29%) patients during the last 12 months of the 2-year accrual period and are the focus of the current study. According to AER, the study cohort was divided into three distinct subgroups: 204 of 834 (24%) patients with long-standing normoalbuminuria, 27 of 109 (25%) patients with new-onset microalbuminuria, and 139 of 312 (45%) patients with prevalent microalbuminuria (22,23). Compared with those not examined by HRV, participants in this analysis did not differ according to age, diabetes duration, sex, systolic BP, hemoglobin A1c (HbA1c), lipid profile, or AER.…”
Section: Selection Of Study Participantsmentioning
confidence: 99%
“…2 Data from several longitudinal studies reported in the 2000s, including several from our group, [3][4][5] began to show that the true evolution of diabetic nephropathy differs from this model. In fact, it has been shown that patients with albuminuria can frequently revert to normoalbuminuria.…”
mentioning
confidence: 99%